2016
DOI: 10.4038/jccp.v47i1.7767
|View full text |Cite
|
Sign up to set email alerts
|

Stroke awareness in a Sri Lankan community Introduction

Abstract: a stroke was the commonest source of knowledge (61.5%). Doctors (32.2%) and other health workers (9.1%) were poor sources of information.Conclusions: Knowledge about stroke is deficient in many aspects. Health professionals need to play a greater role in improving awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There was no significant difference in awareness between adults and schoolchildren, or between those <60 years and ≥60 years of age. 19 There are only a few reports on stroke awareness from South Asia, and this study highlighted many areas of deficient knowledge on stroke in a community setting and the need for comprehensive public education programs.…”
Section: Figure 1 Distribution Of State-sector Hospitals With Neurologists and Stroke Units By Administrative District In Sri Lankamentioning
confidence: 78%
“…There was no significant difference in awareness between adults and schoolchildren, or between those <60 years and ≥60 years of age. 19 There are only a few reports on stroke awareness from South Asia, and this study highlighted many areas of deficient knowledge on stroke in a community setting and the need for comprehensive public education programs.…”
Section: Figure 1 Distribution Of State-sector Hospitals With Neurologists and Stroke Units By Administrative District In Sri Lankamentioning
confidence: 78%
“…It may also point to a lack of sufficient disease knowledge on the part of health workers in Uganda. A study in Pakistan found that junior and future doctors had poor hypertension knowledge leading to sub-optimal management of hypertension cases (21). Another study in Iran showed only 20% of physicians could properly manage a patient with hypertension (22).…”
Section: Discussionmentioning
confidence: 99%
“…There is no data currently available on awareness of TIAs in Sri Lankan patients or the public. Previous studies have shown low levels of awareness of stroke among stroke victims, patients at high risk of stroke, and in the community [34,35], and it is likely that awareness on TIA is similarly low. Awareness of diagnosis and emergency management of TIAs among first contact Sri Lankan doctors is inadequate [20], and efforts should be made to update their knowledge of TIAs and the need for timely referral of patients for specialist opinion.…”
Section: Tia In Sri Lanka: Where Are We and What Can We Do?mentioning
confidence: 97%